The role of protection motivation theory in predicted of nutritional behavior in prevention cancers in mothers in Yazd city, Iran - Baghianimoghadam, Mohammad Hosein; Sharifpour, Zahra; Lotfizadeh, Masoud; Nadjarzadeh, Azadeh; Hashemi, Azam-Sadat; Baghianimoghadam, Behnam (Progress in Nutrition, 2014)
Introduction: Currently, cancer is one of the most important health concerns-care in the world and Iran. The causes of cancer can be effective in creating things like the environment, food, genetics, hormones, viral factors, sunlight, smoking, weight and physical activity. In this study for first time the Protection motivation theory was applied in nutrition behavior that are important in prevention of cancers. Materials and Methods: This was a cross-sectional and descriptive study. The participants were from 18 health centers, 9 health centers was selected and from every health center, 24 mothers were selected by simple sampling. The data was collected by a researcher making questionnaire that was completed by participants. After completion of questionnaires, all gathered data were transferred to SPSS 16 and analyzed under ANOVA, Chi square, T-test and Pearson tests and descriptive statistics. Results: Subjects were in the age group between 27-40 years. The education of 41.4% of participants was university. There is significant difference between age of participant and Perceived self efficacy (p=0,005). The data showed that the structures of Protection motivation theory could predicted 34.9% of behavior Nutritional Prevention of Cancer that the most of them was for Perceived Rewards with 39%. Discussion: The data of this study showed that protection motivation theory is effective in predicted the nutritional behavior in prevention of cancers. So we can use from this theory for planning the educational program in prevention of unsuitable behavior in prevention of cancers.